Balancing Needs and Autonomy: The Involvement of Pregnant Women's Partners in Decisions About cfDNA. (January 2019) - Farrell, Ruth M.; Mercer, MaryBeth; Agatisa, Patricia K.; Coleridge, Marissa B.
Cell-free fetal DNA (cfDNA) screening is used to identify the presence of fetal genetic variants early in pregnancy. Patients' informed decision-making is central to the success of this new screen in clinical practice. Although research has focused on pregnant women's decision-making, little is known about partners' role and preferences as a member of the decision-making dyad. Using a grounded theory approach, this study analyzed 23 in-depth interviews to examine partners' perspectives about cfDNA screening and preferences with respect to their role in the decision-making process. Participants wished to be actively involved in testing decisions. They articulated a distinct set of needs and preferences in the decision-making process. Such involvement was hindered by several biological and logistical barriers. This study demonstrates the need to develop mechanisms that foster informed decision-making for cfDNA screening and related new reproductive genetic technologies that focus on not just the pregnant woman but also the decision-making dyad that includes her partner as well.